CRISPR-Assisted Multiplex Base Editing System in Pseudomonas putida KT2440 - Sun, Jun; Lu, Li-Bing; Liang, Tian-Xin; Yang, Li-Rong; Wu, Jian-Ping (Frontiers in Bioengineering and Biotechnology, 2020)
Pseudomonas putida (P. putida) KT2440 is a paradigmatic environmental-bacterium that possesses significant potential in synthetic biology, metabolic engineering and biodegradation applications. However, most genome editing methods of P. putida KT2440 depend on heterologous repair proteins and the provision of donor DNA templates, which is laborious and inefficient. In this report, an efficient cytosine base editing system was established by using cytidine deaminase (APOBEC1), enhanced specificity Cas9 nickase (eSpCas9ppD10A) and the uracil DNA glycosylase inhibitor (UGI). This constructed base editor converts C-G into T-A in the absence of DNA strands breaks and donor DNA templates. By introducing a premature stop codon in target spacers, we successfully applied this system for gene inactivation with an efficiency of 25–100% in various Pseudomonas species, including P. putida KT2440, P. aeruginosa PAO1, P. fluorescens Pf-5 and P. entomophila L48. We engineered an eSpCas9ppD10A-NG variant with a NG protospacer adjacent motif to expand base editing candidate sites. By modifying the APOBEC1 domain, we successfully narrowed the editable window to increase gene inactivation efficiency in cytidine-rich spacers. Additionally, multiplex base editing in double and triple loci was achieved with mutation efficiencies of 90–100% and 25–35%, respectively. Taken together, the establishment of a fast, convenient and universal base editing system will accelerate the pace of future research undertaken with P. putida KT2440 and other Pseudomonas species.